2014
DOI: 10.5530/pc.2015.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic toxicity study of methanol leafextract of Cardiospermum halicacabum L and Vitex negundo L in rats

Abstract: Introduction: Cardiospermum halicacabum L and Vitex negundo L are distributed throughout the plains of India and used in traditional practice for the treatment of inflammation and rheumatic disorders. The aim of this study is to evaluate acute and sub-chronic toxicity of methanol leaf extracts of Cardiospermum halicacabum (MLECH) and methanol leaf extract of Vitex negundo (MLEVN). MLECH and MLEVN were evaluated for acute and sub-chronic toxicity in mice and rats respectively. Materials and Methods: The acute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a toxicity study of methanol leaf extract of Vitex negundo in mice, an extract dose of about 2000 mg/kg induced no sign of lethargy, jerk, convulsion, and mortality, while the sub-chronic toxicity investigation reported that a dose of 400 mg/kg was safe for mice. 26 A study in India also described the Acute and sub-chronic dermal toxicity of Vitex negundo essential oil. The research also revealed that behavioral, biochemical, haematological, and histopathological abnormalities were absent from animals treated with 250 and 1000 mg/kg/day Vitex negundo oil.…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…In a toxicity study of methanol leaf extract of Vitex negundo in mice, an extract dose of about 2000 mg/kg induced no sign of lethargy, jerk, convulsion, and mortality, while the sub-chronic toxicity investigation reported that a dose of 400 mg/kg was safe for mice. 26 A study in India also described the Acute and sub-chronic dermal toxicity of Vitex negundo essential oil. The research also revealed that behavioral, biochemical, haematological, and histopathological abnormalities were absent from animals treated with 250 and 1000 mg/kg/day Vitex negundo oil.…”
Section: Histopathological Resultsmentioning
confidence: 99%